2022
DOI: 10.1186/s12870-022-03518-8
|View full text |Cite
|
Sign up to set email alerts
|

De novo assembly of a fruit transcriptome set identifies AmMYB10 as a key regulator of anthocyanin biosynthesis in Aronia melanocarpa

Abstract: Aronia is a group of deciduous fruiting shrubs, of the Rosaceae family, native to eastern North America. Interest in Aronia has increased because of the high levels of dietary antioxidants in Aronia fruits. Using Illumina RNA-seq transcriptome analysis, this study investigates the molecular mechanisms of polyphenol biosynthesis during Aronia fruit development. Six A. melanocarpa (diploid) accessions were collected at four fruit developmental stages. De novo assembly was performed with 341 million clean reads f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…A large number of studies have shown that MYB, bHLH, and WD40 transcription factors were the regulators of flavonoid biosynthesis, and the results also showed that IbMYB1 controls the biosynthesis of anthocyanins in sweet potato [ 71 ]. It was found that 10 anthocyanin biosynthesis genes were significantly up-regulated during Aronia melanocarpa fruit development [ 72 ]. Hence, it shows that anthocyanin biosynthesis related-genes may be involved in the tuberous root development in sweet potato, and their regulatory mechanism should be studied in the next step.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that MYB, bHLH, and WD40 transcription factors were the regulators of flavonoid biosynthesis, and the results also showed that IbMYB1 controls the biosynthesis of anthocyanins in sweet potato [ 71 ]. It was found that 10 anthocyanin biosynthesis genes were significantly up-regulated during Aronia melanocarpa fruit development [ 72 ]. Hence, it shows that anthocyanin biosynthesis related-genes may be involved in the tuberous root development in sweet potato, and their regulatory mechanism should be studied in the next step.…”
Section: Discussionmentioning
confidence: 99%
“…The high-quality fragment reads (quality value ≥20) were spliced by software Trinity (software version number: 2.4.0) ( Jonathan et al, 2022 ). All the assembled unigenes were searched against public protein databases, such as NCBI non-redundant protein sequences (NR) and Swiss-Prot for homology comparison.…”
Section: Methodsmentioning
confidence: 99%
“…All the assembled unigenes were searched against public protein databases, such as NCBI non-redundant protein sequences (NR) and Swiss-Prot for homology comparison. Only those matches with E-value below 10–5 were deemed significant ( Park et al, 2021 ; Jonathan et al, 2022 ). Furthermore, gene function prediction and classification were assigned based on the database of the Gene Ontology (GO) and Eukaryotic Orthologous Groups of proteins (KOG).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that kiwifruit [2,3], kumquat [4], tomato [5][6][7], apple [8], carrot [9], banana [10], and apricot [11] contain major accumulations of carotenoids. Furthermore, anthocyanins mainly accumulate in mulberry [12], Chinese Jujube [13], Chokecherry [14], peach [15], citrus [16], grape [17], persimmon [18], black chokeberry [19], eggplant [20], and onion [21].…”
Section: Introductionmentioning
confidence: 99%